Effects of chronic use of proton pump inhibitors (Research, Society and Development, 2024)
Proton pump inhibitors (PPIs) act by inhibiting the enzyme H+/K+ ATPase, significantly reducing gastric acid production and lowering stomach pH. Therefore, they are considered the first-line treatment for gastrointestinal reflux disease and Barrett's esophagus, as well as being considered in the treatment of other conditions such as H. pylori infection and eosinophilic esophagitis. They are drugs with infrequent adverse effects and easy access, as no prescription is required to acquire them. These factors contribute to their indiscriminate use and consequently the emergence of deleterious effects on human health. This study is an integrative literature review, gathering published data on the chronic effects of proton pump inhibitors. Articles published in national and international journals related to scientific research were used. Based on the identification of the problem, the thematic bases of the study were defined, and literary references that met the inclusion criteria were selected. Then, the information was synthesized. The databases used for the study were Scielo, Public Medline, and PubMed. Therefore, this literature review aims to explore various available studies on the effects of chronic use of proton pump inhibitors, with the goal of encouraging further scientific production on this topic and subsequently guiding clinical practice.